Chemotherapeutic Approaches Against Trypanosoma evansi: Retrospective Analysis, Current Status and Future Outlook - S. Rathore, Nitu; Manuja, Anju; Kumar Manuja, Balvinder; Choudhary, Shalki (Current Topics in Medicinal Chemistry, 2016)
Trypanosoma evansi, the causative agent of surra, is pathogenic to a wide variety of wild and domestic animals, including equines, camels, goats, sheep, cattle, buffaloes, pigs, dogs, tigers, elephants etc. The infection is mainly restricted to animals but ability to infect human beings has also been reported due to the lack of efficient apolipoprotein L 1. The parasite is mechanically transmitted by blood-sucking flies such as Tabanus and Stomoxys species. The disease has a major economic impact in tropical countries. The control of trypanosomosis may be aimed either at the fly or against the parasite. Due to difficulties in large scale fly control, trypanocides have been widely used to control the disease. However, current chemotherapeutic agents are limited in number and usually associated with severe side effects. Moreover, current therapeutic agents are far from ideal. The emergence of drug resistant trypanosomes results in failure of prophylaxis and treatment of the disease. Retrospective and prospective studies on drug and delivery against T. evansi will provide an overview of the chemotherapeutic and prophylactic measures in vogue and suggest future strategies for combating this neglected disease. In this perspective, we have reviewed the currently used drugs available for prophylaxis and therapy, their mechanism of action and associated limitations. The options available for prophylaxis and therapy along with potential new molecules/therapeutic agents and novel approaches for delivery of the drugs to enhance their therapeutic value are presented in this review.
Keywords: Trypanocidal drugs